Edukasi Kesehatan Pencegahan Hipertensi untuk Masyarakat Sehat di Wilayah Kerja Puskesmas Banguntapan III, Bantul, Yogyakarta: Health Education on Hypertension Prevention for Healthy Communities in the Work Area of Banguntapan III Community Health Center, Bantul, Yogyakarta - Mudayana, Ahmad Ahid; Widyaningrum, Retno; Kusuma, Oksa Wijaya; Dilansari, Vina Annisa; Dewi, Citra Kusuma; Febiyana, Christi; Prabowo, Afriyan Randhi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
WHO explains that the number of cases of hypertension is estimated at 1.28 billion adults aged 30-79 years worldwide suffering from hypertension, 2/3 live in countries with low and middle levels. WHO also stated that treatment coverage must be >76 million people to be treated. This must be achieved by 2050. Based on the 2018 Riskesdas results, the prevalence of hypertension in the population aged >18 years in Indonesia showed that 658,201 sufferers were diagnosed with hypertension. Based on profile data from the Puskesmas Banguntapan III, 568 patients have been diagnosed with hypertension as of 2022. Based on these problems, health education related to this was held from June 22 to July 6, 2024. There were pre-test and post-test activities to see the level of knowledge of the respondents, it was seen that residents were very enthusiastic about participating in this activity.